Between ‘the me that leaves and the me that returns’: Gertrude Bell’s Persian Gateways and Walls - Julia Szołtysek (Postscriptum Polonistyczne)
Persian Pictures, Gertrude Bell’s first published collection, differs substantially from her later works; critics have accused it of sentimentality, lack of substance – a mere ‘folly’ incommensurable with Bell’s later writings. In the present article, I intend to advocate for Bell, though, proposing to see the supposed faults of Persian Pictures as the work’s greatest strengths which in fact reveal the author’s other, more lyrical and less ‘business-like’, side. With special emphasis placed on the concept of gateways and walls I will attempt to shed light on how, by traversing and/or transgressing borders of various types and putting herself to a series of identity-forming tests, Persian Pictures – to the contemporary reader – offer insight into the broader apparatus of British (and Western) colonialism. By linking each of the selected essays with one of John Frederick Lewis’s orientalist paintings, I hope to further strengthen my argument that aspects of Persian Pictures, originally seen as the work’s weaknesses, have the potential to actually enrich discussions of Western mis/representations of the Orient, without compromising its author, and should thus be approached as instances of powerful and vivid responses to the ‘shock of the new,’ as experienced by Gertrude Bell – and, in fact, many other travellers, male and female alike, who ventured into these realms.